KAJIAN TEKNIK VOKAL LAGU “CEMBURU” KARYA DEWA 19 DALAM INTERPRETASI GRUP MUSIQMATES - Rahman, Sitriandika; Mimy Astuty Pulukadang; La Ode Karlan (SINERGI : Jurnal Riset Ilmiah, 2025)
This study discusses the Study of Vocal Techniques in the song "Cemburu" by Dewa 19 interpreted by Musiqmates. The purpose of this study is to find out how MusiqMates interprets Vocal Techniques in the song "Cemburu". The research method used is descriptive qualitative with a case study approach. Data were obtained through observation of audio recording analysis, video analysis, as well as interviews and literature studies related to vocal techniques. The results of the study show that Musiqmates' interpretation uses several Vocal Techniques such as Chest Voice, Belting Voice, Vibrato and Voice dynamics that are slightly different from the original version, creating a new nuance. This difference shows the existence of artistic freedom in the interpretation of the song as well as a deep understanding of the character of the song by Musiqmates. This study is expected to be useful for the field of vocal interpretation science in Indonesian popular music, and provide contributions to artists, especially solo singers, band vocalists, vocal coaches, and students or students majoring in music/vocal. can contribute to the study of vocal interpretation in Indonesian popular music.